Determination and Seasonal Variation of Heavy Metals in Algae and Sediments in Sewers from Industrial Areas in Lagos State, Nigeria (Biological Sciences - PJSIR, 2005)
The level of heavy metals (Cd, Pb, Cu and Zn) in algae and sediments in sewers from industrial areas was determined by atomic absorption spectrophotometry (AAS). In order to evaluate the metal load of the sewers, as a result of discharged effluents, algae and sediments were collected from three major industrial areas in Lagos, Nigeria during the two main seasons (rainy and dry). Using total digestion, the mean concentration of Cd, Pb, Cu and Zn in algae at Oshodi/ Isolo industrial area for the two seasons respectively ranged from 0.04-0.15 mg/g, 0.32-1.86 mg/g, 0.42-1.52 mg/g and 0.10-1.80 mg/g, while those in sediments ranged from not detectable (ND)-0.10 mg/g, 0.12-1.32 mg/g, 0.21-2.65 mg/g and 0.18-1.74 mg/g, respectively. At Iganmu industrial area, the range in algae was ND-0.21 mg/g, 0.20-1.84 mg/g, 0.17- 1.90 mg/g and 0.05-1.87 mg/g, while those in sediments was 0.04-0.50 mg/g, 0.22-1.85 mg/g, 0.15-1.78 mg/g and   0.48-2.86 mg/g in the same metal order. The range in algae at Ikeja industrial area was 0.05-0.18 mg/g, 0.08-0.82 mg/g, 0.51- 1.40 mg/g and 0.24-2.80 mg/g, while the sediments recorded a range of 0.04-0.60 mg/g, 0.16-0.90 mg/g, 0.24-2.35 mg/g and 0.23-2.84 mg/g, in the respective metal order. Levels of the metals were higher in most samples during the dry season and there were significant differences in the metal concentrations from industrial and residential areas.